(Acetylacetonato‐κ2O, O′)(2, 2′‐bipyridine‐κ2N, N′)iodidocopper(II): a compound with two molecules in the asymmetric unit due to different π–π interactions. (5th August 2013) - Diniz, Lorrane; Carvalho, Sandra; Borges, Ruth H. U.; Rodrigues, Bernardo L.
Abstract : The crystal structure of the title complex, [Cu(C5 H7 O2 )I(C10 H8 N2 )], in the space group P with Z = 4, is stabilized by π–π interactions and weak C—H...I interactions. The presence of two molecules in the asymmetric unit is associated with different intermolecular π–π interactions between two symmetry‐related molecules of each type.